An Evaluation Study of Staff-User Interaction in Academic Libraries - Ugochi Nnenna Ndoh (Journal of Learning and Educational Policy, 2023)
The goal of this study is to determine the degree of interaction between librarians and those who utilize the resources provided by a university library from the perspective of the users themselves. Specifically, this investigation will focus on the patrons who use the library. More specifically, the study will concentrate on clients of libraries and how they see the interaction that occurs between librarians and themselves. By switching to a strategy that focuses on simultaneous explanations, it demonstrates the characteristics of both qualitative and quantitative research. It indicates that in order to put the proposal into practice, library administrators should pay close attention to the significance of offering staff training sessions on how to communicate with patrons who have impairments. These sessions should focus on how to communicate with customers who have hearing, vision, or other types of impairments. The purpose of these workshops need to be to teach participants how to interact effectively with clients who have hearing, visual, or other types of impairments. The study has also found crucial traits that are relevant to the difficulties in communication that emerge from external sources. These characteristics include: According to the definitions of gaps that are provided by the SERVQUAL model, the most likely reasons for a communications gap are caused when there is a discrepancy between the aims of service delivery and what is conveyed. This discrepancy can occur when there is a disconnect between what is intended to be communicated and what is actually communicated. This disparity may arise if there is a gap between the message that was meant to be sent and the one that was actually communicated.